2005
DOI: 10.1557/proc-0900-o03-08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Oxide Nanocrystals in Media Containing E. coli and C. xerosis Bacteria

Abstract: The present investigation is centered on the study of the growth curves of E. coli and C. xerosis bacteria in the presence of nanosize particles of Zinc Oxide. Previous works demonstrated the sensitivity of the bacteria, when these were reproduced in media that contain nanoparticles of luminescent silicon and Cobalt Ferrite. Doped ZnO nanocrystals were synthesized by conventional precipitation in ethanol solutions as reported by Spanhel and Anderson for bare ZnO. In our case, the syntheses were carried out und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It has also been reported that electrons generated by nanoparticles may enhance enzymatic function of external membrane proteins, may speed up electron transport chain function, and facilitate cell metabolism. Some of the studies have also shown no noticeable influence of nanoparticles on bacteria [25,58].…”
Section: Toxicity Of Metal Oxide-based Nanoparticlesmentioning
confidence: 99%
“…It has also been reported that electrons generated by nanoparticles may enhance enzymatic function of external membrane proteins, may speed up electron transport chain function, and facilitate cell metabolism. Some of the studies have also shown no noticeable influence of nanoparticles on bacteria [25,58].…”
Section: Toxicity Of Metal Oxide-based Nanoparticlesmentioning
confidence: 99%
“…Nanoparticles (NPs) have been hypothesized to be influence microbial production, growth and survival. Previous reports evidenced the effect of different NPs on the growth and secondary metabolite production in various microorganisms [ 8 , 9 ]. But reports revealed that NPs like Ag, Au and oxides of Al, Ti, Si and Zn have detrimental effect on the cells of microorganisms [ 10 ].…”
Section: Introductionmentioning
confidence: 99%